Analysis of the public transport system and air pollution of light vehicles in the city of Tacna - 2014. - Arcaya Pancca, Pablo Cesar (2016)
Objective: This research aims to analyze the system of public transport and air pollution light vehicles in the city of Tacna - 2014. Method: The methodology used was through the collection of information on air pollution, by the Regional Government of Tacna, such as project monitoring air quality in the region of Tacna to verify that the data collected meet environmental quality standards and permissible limits and the company Cortec SRL Technical Reviews for light vehicles in the city of Tacna, to know how much of gasolineros and oil vehicles meet technical reviews during the months of 2014 and surveys the population to know your opinion on the contamination of light vehicles. Results: The results were that the values of Particulate Matter 2.5 (ug / m3), exceed the environmental quality standards (ECA), in the districts of Alto de la Alianza (ISTP Francisco de Paula Gonzalez Vigil-Av Jorge Basadre. ), New Town (Health Centre New Town-Street Daniel Alcides Carrión) and Tacna (Gran Hotel Tacna Av. Bolognesi), where there are oil and old vehicles that pollute more air, and there is ignorance on the part of the authorities regarding air pollution caused by light vehicles. Conclusion: It came to the general conclusion that is required to take measures to reduce air pollution, and have obtained historical information pollution versus increased fleet